Educational Problems in Islamic Boarding Schools: A Philosophical Study of Tradition and Modernity - Moh Rafli Idris; Abdul Muqit (Kamil : Journal of Education, 2026)
This research aims to examine the problems of education in Islamic boarding schools from a philosophical perspective by highlighting the dialectic between tradition and modernity. Pesantren as the oldest Islamic educational institution in Indonesia faces a double challenge: maintaining traditional values rooted in spirituality and manners, while adapting to the currents of modernity that demand methodological innovation, rationality, and efficiency. This research uses a library research approach by examining academic literature, scientific journals, and contemporary researchers on Islamic boarding school transformation. The results of the study show that the problems of Islamic boarding school education include epistemological, methodological, and axiological aspects. Epistemologically, Islamic boarding schools are still trying to unite religious science and general science in an integrative scientific paradigm. Methodologically, Islamic boarding schools face challenges in adapting modern technology and learning systems without ignoring the characteristics of the typical teacher-student relationship.